2016
DOI: 10.3390/molecules21030290
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD44 and ERM Proteins in Expression and Functionality of P-glycoprotein in Breast Cancer Cells

Abstract: Multidrug resistance (MDR) is often attributed to the over-expression of P-glycoprotein (P-gp), which prevents the accumulation of anticancer drugs within cells by virtue of its active drug efflux capacity. We have previously described the intercellular transfer of P-gp via extracellular vesicles (EVs) and proposed the involvement of a unique protein complex in regulating this process. In this paper, we investigate the role of these mediators in the regulation of P-gp functionality and hence the acquisition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…EVs have also been shown to modulate the anti-tumoral response by affecting the immune response, T-cell activation and natural killer cell induction (30)(31)(32)(33). EVs can also contribute to drug resistance via various mechanisms, including the sequestration of drugs (34,35) and the transfer of proteins or RNA (36)(37)(38)(39) (40)(41)(42)(43)(44)(45). The morphology and the proteomic profile of EVs from multi-drug resistant tumours has been shown to be different from those from sensitive tumours (46) and EVs could be used as prognostic and diagnostic biomarkers in cancer (47).…”
mentioning
confidence: 99%
“…EVs have also been shown to modulate the anti-tumoral response by affecting the immune response, T-cell activation and natural killer cell induction (30)(31)(32)(33). EVs can also contribute to drug resistance via various mechanisms, including the sequestration of drugs (34,35) and the transfer of proteins or RNA (36)(37)(38)(39) (40)(41)(42)(43)(44)(45). The morphology and the proteomic profile of EVs from multi-drug resistant tumours has been shown to be different from those from sensitive tumours (46) and EVs could be used as prognostic and diagnostic biomarkers in cancer (47).…”
mentioning
confidence: 99%
“…Selected differentially regulated protein spots were excised from gels, trypsin digested, and analyzed by LC/MS/MS according to Pokharel et al (2016). Using an autosampler, connected to a nanoLC system (Tempo Eksigent, USA), 10 μL of the sample was loaded at 20 μL/min with MS loading solvent (2% Acetonitrile + 0.2% Trifluoroacetic Acid) onto a C8 trap column (CapTrap.…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated Radixin and CD44 are required for regulating P‐gp‐mediated drug efflux in drug resistant breast cancer cells. Moreover, silencing experiments carried out on the recipient cells showed that ERM proteins Ezrin and Moesin are required for the intercellular membrane insertion of P‐gp . Demonstrating for the first time that the intercellular EV‐mediated transfer of P‐gp in the recipient cell is dependent on Ezrin and Moesin, however, functionality is governed by the integrity of the ERM complex (Figure (5)).…”
Section: Proteins Regulating Classical Mdrmentioning
confidence: 99%